Structure, histochemistry and ultrastructure of the male reproductive accessory glands in the neotropical flat-faced fruit-eating bat Artibeus planirostris (Chiroptera: Phyllostomidae) - Puga, Cíntia C. I. [UNESP]; Beguelini, Mateus R. [UNESP]; Negrin, Ana C. [UNESP]; Christante, Caroline M. [UNESP]; Morielle-Versute, Eliana [UNESP]; Vilamaior, Patricia S. L. [UNESP]; Taboga, Sebastião R. [UNESP] (CSIRO Publishing, 2013)
Chiroptera, the second largest mammalian order, presents different reproductive strategies and unique reproductive features. However, there are few reports regarding male reproductive accessory glands (RAGs) in Chiroptera. Thus, the aim of the present study was to characterise the RAGs of the exclusively neotropical bat Artibeus planirostris (Chiroptera: Phyllostomidae) macroscopically, microscopically and ultrastructurally. The RAGs were composed of a prostatic complex with two regions (ventral and dorsal) and paraurethral and bulbourethral glands, but no seminal vesicles. The ventral region had an undefined epithelium, with secretory and basal cells, and its secretions were periodic acid-Schiff (PAS) positive. The dorsal region received both deferens ducts, had a columnar pseudostratified epithelium with secretory and basal cells. There were two types of secretions from the dorsal region: one that was basophilic and another that was mixed PAS positive and PAS negative. The paraurethral glands were dispersed in the connective tissue of the urethra, whereas the bulbourethral glands were located in the penile root. Histological and ultrastructural data confirmed the prostatic nature of the ventral and dorsal regions and the holocrine nature of the ventral region, with the latter finding never having been described previously for the prostate gland. Our findings demonstrate the wide discrepancy of RAGs between A. planirostris and other mammals in terms of their composition, structure and morphology. © CSIRO 2013.
Keywords: bulbourethral; paraurethral gland; prostate; accessory sex gland; Artibeus planirostris; basal cell; basophil; bat; bulbourethral gland; connective tissue; epithelium cell; histochemistry; male; male genital system; Neotropics; nonhuman; paraurethral duct; penis; secretory cell; tissue structure; ultrastructure; vas deferens; Animals; Brazil; Bulbourethral Glands; Chiroptera; Epithelium; Genitalia, Male; Imaging, Three-Dimensional; Male; Microscopy, Electron, Transmission; Prostate; Testis